Development of Goods Purchase Information System Using the Waterfall Model - Nur Hidayati (IJISTECH (International Journal of Information System and Technology), 2022)
Purchasing has an important role in a company, where by purchasing the goods needed in the company it will maintain the existing inventory. If the supply of goods is fulfilled in the company then activities in other fields such as sales will be able to run. So that the company will always get income or income. At the present time, there are still many purchasing data processing that are still not computerized or done manually. This of course can cause problems in the field of purchasing systems such as errors in matching data when the goods ordered are received, errors in data recording and even making purchase reports takes a long time and the resulting information is inaccurate. If obstacles like this are allowed to continue, of course, it can cause losses to the company and the information conveyed is less accountable. Because it is necessary to have a system development in the purchasing information system, so that these constraints can be resolved and get the best solution so that the company can still compete and run as expected. To assist the development of the system, it is necessary to determine the right model and. the use of the waterfall model can be one of the best choices in developing the system. With the use of this waterfall model, it can be seen clearly the steps in the development of the system so that it is hoped that the end result can create an application that can be implemented in a goods purchasing information system.